Koran kak filosofija prava - Sandybayev, Zh. (Chabaršy. Dintanu serijasy, 2023)
In this article, the author writes that the Koran is not only an important source of theological and moral values ​​and norms for the Muslim world, but also the basis of the philosophy of law. The Qur'an reinforced the foundation of traditional moral values ​​that were consistent with its principles. However, the Prophet Muhammad, as an innovative teacher of his time, clearly understood that a radical change in the existing order in society would not bring the desired result. Therefore, Islam welcomed moral norms and values ​​that are in harmony with the fundamental principles of Islam. The author, referring to the well-known verses from Surah al-Fatiha: "Lead us in the right way. By the path of those whom You have favored…" (Quran 1:6-7) concludes that the Quran is "a guide to the right path." And if the Koran is perceived as a book indicating the right path, then, of course, it contains many rules, norms and principles. A society that aims to follow the right path needs a code of principles that would evaluate deeds, actions and customs, and also determine whether they are right or wrong. The Qur'an, according to the author, provides such a set of principles. In this regard, the author puts forward the idea that the Koran is a collection of legal norms and ethical rules.